2022
DOI: 10.1055/s-0042-1743094
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence Suffered by Women in Early and Late Adolescence: Care Provided and Follow-Up

Abstract: Objective To compare the sexual violence suffered by women in early and late adolescence, the reactions triggered after the aggression, and the care provided. Methods A retrospective study in which we reviewed the medical records of 521 female adolescents treated by a multidisciplinary team at a reference hospital in the city of Campinas, state of São Paulo, Brazil. We analyzed sociodemographic variables, and those pertainin to the characteristics of the episodes of violence, the emergency care, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…A study that investigates the prevalence of intimate partner violence among women in São Paulo demonstrated that 55.7% of women had experienced some form of violence during their lifetime, 12.4% of that related to sexual violence. (18) Domestic crimes were the most frequent ones (56.1%), in agreement with the findings of other similar studies in Brazil (11,15) . It may be explained by the fact that the Marteli et.…”
Section: Discussionsupporting
confidence: 91%
“…A study that investigates the prevalence of intimate partner violence among women in São Paulo demonstrated that 55.7% of women had experienced some form of violence during their lifetime, 12.4% of that related to sexual violence. (18) Domestic crimes were the most frequent ones (56.1%), in agreement with the findings of other similar studies in Brazil (11,15) . It may be explained by the fact that the Marteli et.…”
Section: Discussionsupporting
confidence: 91%
“… 5 6 7 In the first weeks after abuse, physical pain, and mental disorders—such as posttraumatic stress disorder, depressive and anxious symptoms—are described in most women. 8 9 Studies describe forms of self-harm, such as cutting, and suicidal ideation/behavior. 1 2 3 9 A study described, in girls aged 12 to 17 years, an association between sexual abuse suffered in childhood and the development of the use of substances, alcohol and other drugs, and aggressive behavior; and supporting the need to address the issue of risk behaviors during the follow-up of survivors of sexual abuse.…”
Section: Introductionmentioning
confidence: 99%
“… 8 9 Studies describe forms of self-harm, such as cutting, and suicidal ideation/behavior. 1 2 3 9 A study described, in girls aged 12 to 17 years, an association between sexual abuse suffered in childhood and the development of the use of substances, alcohol and other drugs, and aggressive behavior; and supporting the need to address the issue of risk behaviors during the follow-up of survivors of sexual abuse. 7 These situations can decrease women's quality of life.…”
Section: Introductionmentioning
confidence: 99%